Participatory Action Research on a Remote Teaching Practicum - Montebon , Darryl Roy T.; Renon, Mike Angel T.; Santos , Victoria J. Delos; UbiÃ±a , Marilou M. (Indonesian Research Journal in Education |IRJE|, 2023)
The pandemic has adversely affected teaching practicum as a culminating activity of pre-service teacher training. Teacher education institutions were forced to transform their programs into flexible modalities rapidly. In this participatory action research, the institutional remote practicum program was developed according to the preparation, actualization, mentoring, and evaluation phases. The researchers used qualitative and mixed-method strategies in certain research phases. The data gathered implied that the remote practicum program developed can be an example of how to implement the different guidelines and policies for flexible practice teaching. Pre-service teachers' experiences in the implementation of the research seem to indicate that the program is responsive to their preparations as beginning teachers. The results also imply that the program's performance is efficient and effective.